Origin & History of ASP SaaS, PaaS and Cloud Computing - Matana, Tony (International Journal of Scientific Research and Management (IJSRM), 2024)
This research paper outlines the evolution of cloud computing and software-as-a-service (SaaS) from their origins in 1960s time-sharing systems to microkernel based systems in the late 1980’s. It traces key developments during the period from 1987 to 1988 including the emergence of an Application Service Provider system. It uses methods and models to confirm accuracy of these claims. The paper highlights how the simple migration from mainframe to microkernels overcame the limitations of adoption by the public, ultimately leading to the dominance of SaaS and PaaS as primary models for delivering software and ASP services. This progression represents in a shift towards more flexible, scalable, and accessible computing models that are delivered by services models, by network with management platforms for software as a service (SaaS), platforms as a service (PaaS) and infrastructure as a service (IaaS) customization.